Cameroon’s logging industry: structure, economic importance and effects of devaluation - Eba'a Atyi, R. (Center for International Forestry Research, 1998)
The current study was conducted in Cameroon from July 1996 to June 1997. In general, it aims to describe the current structure of the Cameroon logging industry, assess its importance within Cameroon's economy, and analyse recent developement which the industry has experienced since the devaluation of the CFA franc in January 1994. Study method consisted mainly of carrying out a structural survey of logging enterprises based on a trialled, written questionnaire, reviewing existing documentation within the forestry administration and timber exporting organisations, and conducting an elementary statistical analysis of the information gathered